A critical analysis of the role of wait time in classroom interactions and the effects on student and teacher interactional behaviours. Issue 1 (2nd January 2016) - Ingram, Jenni; Elliott, Victoria
Abstract : Extending the pauses between teachers' and students' turns (wait time) has been recommended as a way of improving classroom learning. Drawing on the Conversation Analysis literature on classroom interactions alongside extracts of classroom interactions, the relationship between these pauses and the interactional behaviour of teachers and students is examined. Extended wait time is built in to classroom interactions because of the IRF (Initiation–Response–Feedback/Follow-up) framework that dominates these interactions. Extending wait time can lead to a variety of changes in the norms of classroom interaction. The structures of interactions in formal classrooms are used to explain the previous findings relating to the extension of wait time. It is also shown that different uses of extended wait time lead to different interactional norms and maintaining extended wait times may not be desirable. Consequently, the article argues for a more nuanced understanding of wait time, desired student behaviours and the interaction of the two.